Tacrolimus concentration/dose ratio as a therapeutic drug monitoring strategy: the influence of gender and comedication - Rančić, Nemanja; Dragojević-Simić, Viktorija; Vavić, Neven; Kovačević, Aleksandra; Šegrt, Zoran; Drašković-Pavlović, Biljana; Mikov, Momir (Vojnosanitetski pregled, 2015)
Background/Aim. A combination of tacrolimus and other drugs such as corticosteroids has been commonly used immunosuppressive regimens. On the other hand, there is a growing body of evidence that male and female may differ in their response to the equal drug treatment. The aim of the study was to estimated the use of tacrolimus concentration/dose (C/D) ratio for the assessment of the influence of gender differences and comedication on tacrolimus exposure in renal transplant recipients. Methods. This prospective case series study included 54 patients, in which the unit of monitoring was outpatient examination (1,872) of the renal transplant patients. The patients were monitored in the period 2010–2014, starting one month after the transplantation. Tacrolimus trough concentrations (TTC) were measured by chemiluminescence microparticles immunoassay. Results. TTC and the tacrolimus C/D ratio were significantly lower in the females comparing with the males. Contrary to the males, in the females a significant increase of the tacrolimus daily dose (TDD) per body weight and TTC, along with the corticosteroid dose increase, was not accompanied by any significant changes in the tacrolimus C/D ratio; in different corticosteroid doses faster elimination of tacrolimus was found with the exception of the doses > 0.25 mg/kg. In the patients treated with proton pump inhibitors, mainly with pantoprazole TDD per body weight and TTC were significantly higher, while the tacrolimus C/D ratio was significantly lower compared to the patients without this treatment. In the patients treated with calcium channel blockers, TDD per body weight was significantly lower (particularly with amlodipine) while the tacrolimus C/D ratio was higher compared to the patients who were not treated by them. Conclusion. A lower tacrolimus exposure was detected in females in comparison to males. When gender differences were considered in the context of different corticosteroid doses, faster elimination of tacrolimus in the females was also seen, with the exception of the doses > 0.25 mg/kg. Tacrolimus exposure in the pantoprazole-treated patients was significantly less expressed, while in patients treated with CCB amplodipine the tacrolimus C/D ratio was significantly higher in comparison with the patients not treated with them.
Keywords: kidney transplantation; tacrolimus; immunosuppres-sive agents; drug therapy; combination; dose-response relationship; drug; sex